1997
DOI: 10.1111/j.1439-0507.1997.tb00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole: comparison of pharmacokinetics, therapy and in vitro susceptibility

Abstract: Fluconazole shows good penetration into the tissues and body fluids examined and a rapid equilibrium is achieved between the concentrations in the various compartments. The pharmacokinetics of fluconazole after intravenous or oral administration are proportional to the dose. This finding, together with the slow elimination of the triazole (t1/2 30 h), makes it easier to forecast the therapeutically effective dosage. Measurements of fluconazole concentration in blood can be used to predict levels in some tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 27 publications
0
27
0
1
Order By: Relevance
“…The pericardial fluid/plasma concentration ratios of fluconazole in 20 patients ranged from 0.9 to 1.0 (136). Data from a single patient with disseminated aspergillosis also suggest that voriconazole diffuses into the pericardial fluid, at a concentration comparable to the plasma concentration (153).…”
Section: Heartmentioning
confidence: 79%
See 2 more Smart Citations
“…The pericardial fluid/plasma concentration ratios of fluconazole in 20 patients ranged from 0.9 to 1.0 (136). Data from a single patient with disseminated aspergillosis also suggest that voriconazole diffuses into the pericardial fluid, at a concentration comparable to the plasma concentration (153).…”
Section: Heartmentioning
confidence: 79%
“…In 20 patients receiving a single 200-mg dose of fluconazole, the lung tissue/plasma concentration ratio range was 1.1 to 1.6 (136). Similarly, the fluconazole ELF/plasma concentration ratio in cats was 1.2 (137).…”
Section: Lungmentioning
confidence: 85%
See 1 more Smart Citation
“…In a prospective, randomized, placebo-controlled trial, fluconazole at a dosage of 400 mg/day was shown to significantly reduce fungal colonization, superficial and hematogenous candidiasis, and mortality [2]. Because fluconazole is well absorbed from the gastrointestinal tract, and there is little associated toxicity [3], this anti-fungal agent is now widely used in chemoprophylaxis in cases involving a risk of opportunistic mycoses.…”
Section: Introductionmentioning
confidence: 99%
“…Penetration into other body tissues such as joint spaces, saliva, vaginal secretions, and vitreous humor of the eye also approximate levels found in the serum. Fluconazole is eliminated primarily through the kidneys and excreted largely unchanged resulting in urine concentrations 10-20 times higher than those found in blood [53,54].…”
Section: Pharmacologymentioning
confidence: 99%